Functional Analysis and Genome Mining Reveal High Potential of Biocontrol and Plant Growth Promotion in Nodule-Inhabiting Bacteria Within Paenibacillus polymyxa Complex - Ali, Md. Arshad; Lou, Yang; Hafeez, Rahila; Li, Xuqing; Hossain, Afsana; Xie, Ting; Lin, Li; Li, Bin; Yin, Yanni; Yan, Jianli; An, Qianli (Frontiers in Microbiology, 2021)
Bacteria belonging to the genus Paenibacillus were frequently isolated from legume nodules. The nodule-inhabiting Paenibacillus as a resource of biocontrol and plant growth-promoting endophytes has rarely been explored. This study explored the nodule-inhabiting Paenibacillus’ antifungal activities and biocontrol potentials against broad-spectrum important phytopathogenic fungi. We collected strains which were isolated from nodules of Robinia pseudoacacia, Dendrolobium triangulare, Ormosia semicastrata, Cicer arietinum, Acacia crassicarpa, or Acacia implexa and belong to P. peoriae, P. kribbensis, P. endophyticus, P. enshidis, P. puldeungensis, P. taichungensis, or closely related to P. kribbensis, or P. anseongense. These nodule-inhabiting Paenibacillus showed diverse antagonistic activities against five phytopathogenic fungi (Fusarium graminearum, Magnaporthe oryzae, Rhizoctonia solani, Sclerotinia sclerotiorum, and Botrytis cinerea). Six strains within the P. polymyxa complex showed broad-spectrum and potent activities against all the five pathogens, and produced multiple hydrolytic enzymes, siderophores, and lipopeptide fusaricidins. Fusaricidins are likely the key antimicrobials responsible for the broad-spectrum antifungal activities. The nodule-inhabiting strains within the P. polymyxa complex were able to epiphytically and endophytically colonize the non-host wheat plants, produce indole acetic acids (IAA), and dissolve calcium phosphate and calcium phytate. P. peoriae strains RP20, RP51, and RP62 could fix N2. P. peoriae RP51 and Paenibacillus sp. RP31, which showed potent plant colonization and plant growth-promotion competence, effectively control fungal infection in planta. Genome mining revealed that all strains (n = 76) within the P. polymyxa complex contain ipdC gene encoding indole-3-pyruvate decarboxylase for biosynthesis of IAA, 96% (n = 73) contain the fus cluster for biosynthesis of fusaricidins, and 43% (n = 33) contain the nif cluster for nitrogen fixation. Together, our study highlights that endophytic strains within the P. polymyxa complex have a high probability to be effective biocontrol agents and biofertilizers and we propose an effective approach to screen strains within the P. polymyxa complex.